Development of inoculants for native legumes to improve restoration of disturbed lands - Watkin, Elizabeth; O'Hara, G.; Dixion, K.; Hill, Y. (Kings park and Botanical Garden, 2009)
Legumes are often pioneer species in disturbed sites, in part due to their ability to form symbioses with nitrogen fixing root nodule bacteria (RNB). The work reported here was conducted in the lease area of Shark Bay Salt located within the Shark Bay World Heritage Property. Many sites within this lease have been mined and although the majority have been decommissioned for over 15 years the mined areas remain in a highly disturbed state compared to the surrounding undisturbed flora. The effect of site disturbance on RNB was determined by comparison with adjacent undisturbed areas. Populations of RNB were larger in undisturbed soils than in the disturbed soils. The deficiency of symbiotic microbes in the disturbed soil pits may be a contributing factor to the lack of recruitment of flora from surrounding pristine areas. An aim of this study was to isolate RNB that effectively fix nitrogen with selected legume species to improve their survival on reintroduction to disturbed sites.Numerous RNB effective in N fixation with the legume species tested were isolated from soils collected within the lease area. Several isolates were selected for a multi-strain inoculum for plants introduced into the degraded areas of Shark Bay Salt Lease area. Inoculation resulted in higher plant yields that may improve survival over the months of little or no rainfall. This study demonstrates the potential for RNB inoculation to remediate disturbance in the Shark Bay lease area, and have a role in rehabilitation of other arid regions of Western Australia.